Effectiveness of participatory wellbeing development program for youths of Juvenile Practice and Training Center in the Department of Juvenile Observation and Protection - Srimoragot, Pongsri; Thongteratham, Natma; Phanpop, Namfon (Thai Journal of Nursing, 2023)
The objective of this quasi-experimental research was to examine effectiveness of participatory wellbeing development program for youths of Juvenile Practice and Training Center in the Department of Juvenile Observation and Protection. The sample of 187 youths from five Juvenile Practice and Training Centers was voluntarily selected. Research tools were the wellbeing assessment and the participatory wellbeing development program including food consumption, exercise and physical activity, stress management and emotional coping, smoking cessation and smoke-free environment. Data analysis were performed using descriptive statistics and paired t-test. Results revealed that after implementing the participatory wellbeing development program, youths had significantly better wellbeing than before the implementation at p < .05.